The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.onc.1208193
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 (PAI-1) modifies the formation of aggressive fibromatosis (desmoid tumor)

Abstract: Aggressive fibromatosis is a mesenchymal neoplasm associated with mutations, resulting in beta-catenin-mediated transcriptional activation. We found that plasminogen activator inhibitor-1 (PAI-1) was upregulated fourfold in aggressive fibromatosis. We investigated the ability of beta-catenin to regulate a PAI-1 reporter, and found that PAI-1 is an indirect target. To determine the role of PAI-1 in vivo, a mouse containing a targeted deletion in Pai-1 was crossed with a mouse that develops aggressive fibromatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…While the mechanisms are unclear, the available data suggest that the anti-apoptotic action of PAI-1 plays a crucial role in drug resistance in multiple cancers, likely involving activation of the PI3K/AKT or ERK1/2 signaling pathways, suppression of plasmin generation or caspase-3 activity or regulation of vitronectin-mediated cell adhesion [ 139 , 143 , 216 , 217 ]. It appears, moreover, that the PAI-1-mediated rescue from spontaneous apoptosis in response to serum deprivation or plasminogen-induced cell detachment ( Figure 5 ) may be dependent, in part, on control of plasmin activation and/or inhibition of Fas/Fas ligand-mediated cell death [ 218 , 219 ].…”
Section: Role Of Pai-1 and The Caf/pai-1 Axis In Tumor Survival And C...mentioning
confidence: 99%
“…While the mechanisms are unclear, the available data suggest that the anti-apoptotic action of PAI-1 plays a crucial role in drug resistance in multiple cancers, likely involving activation of the PI3K/AKT or ERK1/2 signaling pathways, suppression of plasmin generation or caspase-3 activity or regulation of vitronectin-mediated cell adhesion [ 139 , 143 , 216 , 217 ]. It appears, moreover, that the PAI-1-mediated rescue from spontaneous apoptosis in response to serum deprivation or plasminogen-induced cell detachment ( Figure 5 ) may be dependent, in part, on control of plasmin activation and/or inhibition of Fas/Fas ligand-mediated cell death [ 218 , 219 ].…”
Section: Role Of Pai-1 and The Caf/pai-1 Axis In Tumor Survival And C...mentioning
confidence: 99%
“…For example, when FVB-PymT mice prone to develop mammary tumors were crossed with PAI-1 null mice, there was no effect on the development of mammary tumors, metastasis, or survival (24). Similarly, genetic ablation of PAI-1 had no effect on tumor development in Apc/Apc1638N mice prone to develop colon cancer (25), in TRP-1SV40 Tag/PAI-1 −/− mice prone to develop ocular tumors (26), and in K14-HPV16/PAI-1 −/− mice prone to develop skin cancer (27). An explanation for this difference of effect between transplanted and GEM mice is the possible presence of compensatory serpins including PAI-2, protein C inhibitor, protease nexin-1, or maspin (28–31), whose overexpression in transformed cells may have compensated for a lack of PAI-1 (27–31).…”
Section: What Have We Learned From Mouse Tumor Models?mentioning
confidence: 99%
“…In contrast to the pro-angiogenic role of PAI1 in physiological conditions, its overexpression in tumoral tissues has an anti-angiogenic function [25]. The effect on proliferation is variable, since PAI1 inhibits proliferation in prostate cancer [26] but increases the tumor size of Hela xenografts, fibromatosis or pheochromocytoma [27][28][29]. Besides, several studies have reported the role of PAI1 as anti-apoptotic in Head-and-Neck Cancer Cells (HNCC), ovarian or breast cancer [19,30].…”
Section: Introductionmentioning
confidence: 99%